If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3n + -22 = -70 Reorder the terms: -22 + 3n = -70 Solving -22 + 3n = -70 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '22' to each side of the equation. -22 + 22 + 3n = -70 + 22 Combine like terms: -22 + 22 = 0 0 + 3n = -70 + 22 3n = -70 + 22 Combine like terms: -70 + 22 = -48 3n = -48 Divide each side by '3'. n = -16 Simplifying n = -16
| -3k^2+12=0 | | 2x+7x=162 | | 21(2.380952381)= | | 2x-12=10x+5 | | 5+4-4q= | | 2b^2-9b=0 | | 5x+3=4x-10 | | 3.14=tan-1(5w)-w | | -10.5=7p | | 45X^2+48X-21=0 | | 7=38 | | 14X^2+21X-35=0 | | X=y^2-13 | | 2y+3+9=11 | | 14X^2+77X+63=0 | | 11x^2-7x+12=0 | | 45X^2+56X-45=0 | | 1x+1=19 | | 27X^2+18X-9=0 | | 4x-2-9=-1 | | 117+57+2x=180 | | 32X^2+88X+56=0 | | 24x+2=-46 | | 72X^2-2X-4=0 | | 8-2(x-4)=3(x-6)+2 | | 0=10x-4.905x^2 | | f(x)=2x^3-10x^2-8x+40 | | 5k^2+5k-14=0 | | 8v^2+12v+5=0 | | 12X^2+15X-63=0 | | log(2x-4)=log(3x+5) | | 10n^2+10n-2=0 |